Butterworth low-pass filter design / Ismahalili Ishak - Ishak, Ismahalili
This work higlighted on the development carried out on miniaturized intergrated filter at center frequency of 10GHz. The design, development and fabrication of Butterworth low-pass filter are accomplished for Rogers Duroids to observe the effect of Iow-k material.Tlic results has revealed that the simulation and measured is comparable as expected. In contrast, the Butterworth low-pass filter for high-k material is focused on the design and the simulation using CAD tools. The result has shown that the physical shape is minimized, the center frequency is reduced to 2.5GHz.